KNOWLEDGE AND ATTITUDE ON SEXUAL BEHAVIOR AMONG BINAKARYA BANGSA VOCATIONAL HIGH SCHOOL STUDENTS - Rosa Susanti; Petrus Geroda Beda Ama; Widi Dwi Asiarini (Siklus : Journal Research Midwifery Politeknik Tegal, 2020)
All children becoming adolescents need information about bodily functions, sexual development, and avoid unwanted pregnancy. Also, they need knowledge about sexually transmitted diseases (STDs), including HIV / AIDS and prevention. This information helps prepare adolescents with their changing. This study used primary data collected by distributing questionnaires to 30 respondents. The finding of this study shows that 66.7% of adolescents are had poor knowledge about reproductive health. The majority of respondents (60%) have a negative attitude towards reproductive health. Furthermore, there is no significant relationship between knowledge and attitude. Keywords: Knowledge, Attitude, Health, Reproduction